Production and Characterization of Healing Polymeric Films for Diabetes Patients’ Wounds - Yakar, Arzu; Dede, Nur (Frontiers in Materials, 2022)
Diabetes-related wounds are a significant problem with serious consequences for both patients and health care systems. The aim of this study is to produce healing films that will expedite the healing of diabetic wounds in order to minimize the negative effects experienced by diabetic patients. For this purpose, films were produced by combining chitosan, which possesses the ability to accelerate wound healing, silver nanoparticles, well-known for their superior properties such as preventing the occurrence of microbiological activity and providing thermal stability, and ascorbic acid, also referred to as vitamin C, which the body requires during the treatment process. The films were evaluated by applying a series of characterization analyzes (XRD, FTIR, TEM, DSC-TGA) to the produced films. In addition, the films were subjected to microbiological tests. Following that, the films’ swelling and ascorbic acid release behaviors were investigated in deionized water and a PBS solution with pH 7.4, respectively.